A new low-power, universal, multi-mode Gm-C filter in CNTFET technology. (August 2019) - Zanjani, S. Mohammad Ali; Dousti, Massoud; Dolatshahi, Mehdi
Abstract: In this paper, a new low-power multi-mode Gm-C universal filter is proposed in carbon nanotube field-effect transistor (CNTFET) technology using only 11 inverters and 2 grounded capacitors. The proposed circuit reduces the power consumption effectively due to the proper use of inverters as operational transconductance amplifier (OTA) blocks. Moreover, the center frequency and quality factor of the proposed filter can be tuned electronically with low sensitivity values. The proposed circuit is simulated in HSPICE using 32 nm CNTFET technology parameters at ±0.2 V supply voltage, and its performance is compared with the circuit proposed in 32 nm CMOS technology. As simulation results show, for certain value of center frequency, the proposed CNTFET filter not only reduces the power consumption by 66%, but also extends the center frequency up to 54%, at the same power consumption value in comparison with 32 nm CMOS technology. Finally, the proposed CNTFET filter benefits from a considerable reduction in chip area.